Neonatal duodenal atresia with heterotopic pancreas: a case report and literature review - Sun, Yinmin; Li, Siqi; Liu, Shiqi; Li, Yufeng; Quan, Dongwen (Frontiers in Pediatrics, 2025)
BackgroundHeterotopic pancreas (HP) is a congenital anomaly characterized by pancreatic tissue entirely separate from the orthotopic pancreas, lacking direct ductal communication and vascular continuity. HP is most frequently found in the upper gastrointestinal tract, particularly the stomach, duodenum, and proximal jejunum, while involvement of the mesentery is relatively rareCase presentationWe report a case of congenital duodenal atresia with concomitant HP in a 3-day-old neonate. Emergency laparotomy was performed at 72 h of life for membranous duodenal atresia; web excision and duodenoduodenostomy were completed. Preoperative evaluation showed no other associated malformations (e.g., congenital heart disease or Down syndrome). Intraoperatively, a 10.0 × 6.0 mm focus of HP tissue was unexpectedly found at the jejunal mesenteric boundary, approximately 5–7 cm distal to the duodenal obstruction, necessitating en bloc resection with a segment of adjacent bowel. Histopathology confirmed HP. During 12-month postoperative follow-up, the neonate remained clinically stable, with physical development consistent with age-matched normal children, and no disease recurrence.ConclusionsGiven the potential association between HP and duodenal atresia in asymptomatic cases, we propose systematic screening for HP in all neonates with this condition. If identified, concurrent prophylactic resection of the HP lesion during the repair of duodenal atresia is recommended to mitigate the risk of long-term complications, including pancreatitis and gastrointestinal bleeding.